PERENCANAAN LANSKAP WISATA SEJARAH UNTUK MENUNJANG ADAPTIVE REUSE GEDUNG JUANG 45 BEKASI JAWA BARAT - Sajiwo, Bagus; Damayanti, Vera Dian (Jurnal Lanskap Indonesia, 2016)
Gedung Juang 45 Bekasi (GJ45B) is a historical site as a legacy from the colonial period, located in Bekasi District, West Java Province. The site has been neglected due to unsuitable site utilization and lack of concern from the local government with respect to preserve the area. The objectives of this study are: (1) to identify the historical value and landscape character of GJ45B, (2) to analyze the potential and constraints of the site to be developed as a historical tourism site, and (3) to develop a concept and site plan for historical tourism of GJ45B site through spatial, circulation, activity, and facility programs which support historical interpretation of the site. The study was conducted through a planning process consisted of preparation, inventory, analysis, concept, synthesis, and site planning. The analysis applied descriptive and spatial approach by using scoring and weighting to physical, historical, and tourism aspects and subsequently resulted three suitability zones for historical tourism development with high, medium, and low values. The conceptual plan for the site is that GJ45B is designed for an educational and recreational historical tourism site by developing historical interpretation of Bekasi District and particularly of GJ45B. The final output of the study is a site plan including spatial, circulation, activities and facilities plans.